Method for synthesizing aluminum nitride fiber through preheating combustion

High aspect ratio aluminum nitride fibers are prepared by preheating combustion synthesis method under low pressure nitrogen, which solves the problems of low fiber aspect ratio and environmental harm of by-products in the existing technology, and realizes low-cost and efficient preparation of aluminum nitride fibers, which are suitable for electronic packaging.

CN120700612APending Publication Date: 2025-09-26TIANJIN UNIVERSITY OF TECHNOLOGY
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510861621.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-25
Publication Date
2025-09-26

AI Technical Summary

Technical Problem

Existing aluminum nitride fiber synthesis methods have problems such as low fiber aspect ratio, product agglomeration, high preparation cost, and environmental harm caused by by-products, which limit their application in electronic devices and energy systems.

Method used

The preheating combustion synthesis method is adopted, with aluminum powder and aluminum nitride as raw materials, and preheating combustion synthesis is carried out under low-pressure nitrogen to increase the combustion reaction temperature and prepare aluminum nitride fibers with a high aspect ratio.

Benefits of technology

The synthesis of high aspect ratio aluminum nitride fibers has been achieved, with a simple process, no by-products, and low preparation cost, and is suitable for high thermal conductivity fillers in electronic packaging.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120700612A_ABST
    Figure CN120700612A_ABST
Patent Text Reader

Abstract

The invention provides a method for synthesizing aluminum nitride fibers by preheating combustion, which comprises the following steps: preheating aluminum powder and aluminum nitride serving as raw materials in a low-pressure nitrogen environment, and then inducing a combustion synthesis reaction to prepare the aluminum nitride fibers with the average diameter of 0.3-0.8 mu m and the average length of 400-800 mu m. The preparation method has the characteristics of simple process, low preparation cost and the like, and the prepared aluminum nitride fiber can be used as a high-thermal-conductivity filler for electronic packaging.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of ceramic materials, and in particular to a method for synthesizing aluminum nitride fibers through preheating and combustion. Background Art

[0002] Aluminum nitride (AN) plays an irreplaceable role in power electronics, microelectronics, aerospace, and other fields due to its exceptional properties, including high intrinsic thermal conductivity, wide bandgap, high resistivity, low dielectric constant, high mechanical strength, chemical stability, and low thermal expansion coefficient. Aluminum nitride fibers, with their unique structural characteristics, are a highly promising high-performance thermal management material due to their high intrinsic thermal conductivity (phonon thermal conductivity), electrical insulation, low percolation threshold imparted by their one-dimensional structure, ability to form an efficient thermal network, and potential anisotropic controllability. Aluminum nitride fibers are a key material for addressing heat dissipation bottlenecks in electronic devices and energy systems, improving device power density, efficiency, and reliability.

[0003] Currently, common methods for synthesizing aluminum nitride fibers include carbothermal reduction, direct nitridation, chemical vapor deposition, and electrospinning. However, these methods suffer from issues such as residual carbon contamination, low fiber aspect ratios, product heteroagglomeration, high production costs, and low yields, which limit their practical engineering applications. Combustion synthesis is considered an economical method for producing AlN powder. This method induces an exothermic reaction between aluminum metal and nitrogen, relying on the inherent heat release of the reaction to complete the synthesis of AlN. It does not require additional, long-term, high-temperature heating and offers advantages such as a short cycle time and low energy consumption. High-quality AlN powder can be synthesized by manipulating process parameters such as raw material ratio, nitrogen pressure, and diluent. Previous studies have reported that combustion synthesis can produce aluminum nitride fibers by reducing reaction pressure and adding additives such as ammonium chloride and ammonium fluoride. However, combustion synthesis still presents challenges in producing aluminum nitride fibers, such as low fiber aspect ratios and the environmental hazards of byproducts such as ammonia and hydrochloric acid produced by the decomposition of additives.

[0004] Therefore, the present invention provides a method for synthesizing aluminum nitride fibers by preheating and combustion, using aluminum powder and aluminum nitride as raw materials, and synthesizing the aluminum nitride fibers by preheating and combustion under low-pressure nitrogen. By preheating the raw materials, the combustion reaction temperature under low nitrogen pressure is increased, thereby achieving the synthesis of high-aspect-ratio aluminum nitride fibers. The preparation method of the present invention has the advantages of simple process, no byproducts, and low production cost. The aluminum nitride fibers produced can be used as high-thermal-conductivity fillers in electronic packaging. Summary of the Invention

[0005] Aluminum nitride (AN) plays an irreplaceable role in power electronics, microelectronics, aerospace, and other fields due to its exceptional properties, including high intrinsic thermal conductivity, wide bandgap, high resistivity, low dielectric constant, high mechanical strength, chemical stability, and low thermal expansion coefficient. Aluminum nitride fibers, with their unique structural characteristics, are a highly promising high-performance thermal management material due to their high intrinsic thermal conductivity (phonon thermal conductivity), electrical insulation, low percolation threshold imparted by their one-dimensional structure, ability to form an efficient thermal network, and potential anisotropic controllability. Aluminum nitride fibers are a key material for addressing heat dissipation bottlenecks in electronic devices and energy systems, improving device power density, efficiency, and reliability.

[0006] Currently, common methods for synthesizing aluminum nitride fibers include carbothermal reduction, direct nitridation, chemical vapor deposition, and electrospinning. However, these methods suffer from issues such as residual carbon contamination, low fiber aspect ratios, product heteroagglomeration, high production costs, and low yields, which limit their practical engineering applications. Combustion synthesis is considered an economical method for producing AlN powder. This method induces an exothermic reaction between aluminum metal and nitrogen, relying on the inherent heat release of the reaction to complete the synthesis of AlN. It does not require additional, long-term, high-temperature heating and offers advantages such as a short cycle time and low energy consumption. High-quality AlN powder can be synthesized by manipulating process parameters such as raw material ratio, nitrogen pressure, and diluent. Previous studies have reported that combustion synthesis can produce aluminum nitride fibers by reducing reaction pressure and adding additives such as ammonium chloride and ammonium fluoride. However, combustion synthesis still presents challenges in producing aluminum nitride fibers, such as low fiber aspect ratios and the environmental hazards of byproducts such as ammonia and hydrochloric acid produced by the decomposition of additives.

[0007] Therefore, the present invention provides a method for synthesizing aluminum nitride fibers by preheating and combustion, using aluminum powder and aluminum nitride as raw materials, and synthesizing the aluminum nitride fibers by preheating and combustion under low-pressure nitrogen. By preheating the raw materials, the combustion reaction temperature under low nitrogen pressure is increased, thereby achieving the synthesis of high-aspect-ratio aluminum nitride fibers. The preparation method of the present invention has the advantages of simple process, no byproducts, and low production cost. The aluminum nitride fibers produced can be used as high-thermal-conductivity fillers in electronic packaging. BRIEF DESCRIPTION OF THE DRAWINGS

[0008] Figure 1 The SEM image of aluminum nitride fiber obtained for Example 4 of the present invention; Figure 2 The SEM image of aluminum nitride fiber obtained for Example 6 of the present invention; DETAILED DESCRIPTION

[0009] Example 1 45wt% aluminum powder (20μm) and 55wt% aluminum nitride powder (5μm) were weighed and mixed uniformly according to the ratio. The mixture was then preheated to 1000°C in a furnace under a nitrogen pressure of 0.2MPa for 30 seconds. The mixture was then ignited to induce a combustion synthesis reaction, and then cooled to produce aluminum nitride fibers. XRD analysis of the sample revealed a pure aluminum nitride phase with no residual aluminum. SEM analysis of the sample revealed an average aluminum nitride fiber diameter of 0.3μm and an average length of 422.3μm.

[0010] Example 2 50wt% aluminum powder (20μm) and 50wt% aluminum nitride powder (5μm) were weighed and mixed uniformly according to the ratio. The mixture was then preheated to 1050°C under a nitrogen pressure of 0.2MPa for 30 seconds. The mixture was then ignited to induce a combustion synthesis reaction. The mixture was then cooled to produce aluminum nitride fibers. XRD analysis of the sample revealed a pure aluminum nitride phase with no residual aluminum. SEM analysis of the sample revealed an average aluminum nitride fiber diameter of 0.4μm and an average length of 484.6μm.

[0011] Example 3 55wt% aluminum powder (20μm) and 45wt% aluminum nitride powder (5μm) were weighed and mixed uniformly according to the ratio. The mixture was then preheated to 1100°C in a furnace under a nitrogen pressure of 0.2MPa for 30 seconds. The mixture was then ignited to induce a combustion synthesis reaction, and then cooled to produce aluminum nitride fibers. XRD analysis of the sample revealed a pure aluminum nitride phase with no residual aluminum. SEM analysis of the sample revealed an average diameter of 0.5μm and an average length of 545.3μm.

[0012] Example 4 60wt% aluminum powder (20μm) and 40wt% aluminum nitride powder (5μm) were weighed and mixed according to the ratio, then placed in a heating furnace, preheated to 1150℃ under a nitrogen pressure of 0.2MPa and kept warm for 30s, ignited to induce a combustion synthesis reaction, and then cooled to obtain aluminum nitride fibers. XRD characterization of the sample showed that it was a pure aluminum nitride phase with no residual aluminum found. SEM characterization of the sample showed that the average diameter of the aluminum nitride fibers was 0.6μm and the average length was 656.8μm. The SEM image is shown in the attached figure. Figure 1 shown.

[0013] Example 5 65wt% aluminum powder (20μm) and 35wt% aluminum nitride powder (5μm) were weighed and mixed uniformly according to the ratio. The mixture was then preheated to 1200°C in a furnace under a nitrogen pressure of 0.2MPa for 30 seconds. The mixture was then ignited to induce a combustion synthesis reaction, and then cooled to produce aluminum nitride fibers. XRD analysis of the sample revealed a pure aluminum nitride phase with no residual aluminum. SEM analysis of the sample revealed an average diameter of 0.8μm and an average length of 698.8μm.

[0014] Example 6 70wt% aluminum powder (20μm) and 30wt% aluminum nitride powder (5μm) were weighed and mixed according to the ratio, then placed in a heating furnace, preheated to 1250℃ under a nitrogen pressure of 0.2MPa and kept warm for 30s, ignited to induce a combustion synthesis reaction, and then cooled to obtain aluminum nitride fibers. XRD characterization of the sample showed that it was a pure aluminum nitride phase with no residual aluminum found. SEM characterization of the sample showed that the average diameter of the aluminum nitride fibers was 0.8μm and the average length was 779.2μm. The SEM image is shown in the attached figure. Figure 2 shown.

[0015] Some embodiments The effect of nitrogen pressure on the synthesis of aluminum nitride fibers was examined. The method and steps were the same as in Example 4, with only the nitrogen pressure being varied. The effect of nitrogen pressure on the synthesis of aluminum nitride fibers is shown in Table 1.

[0016] Table 1 Effect of nitrogen pressure on the synthesis of aluminum nitride fibers Instance number Nitrogen pressure (MPa) Is there any residual aluminum? Morphology of synthesized aluminum nitride 1 0.01 yes particles 2 0.05 yes fiber 3 0.1 no fiber 4 0.2 no fiber 5 0.5 no fiber 6 0.8 no fiber 7 1.0 no fiber 8 1.1 no Fibers, particles 9 1.2 no particles Conclusion: When the nitrogen pressure is less than 0.05 MPa, the low nitrogen content leads to a slow and incomplete reaction, with a large amount of residual aluminum in the product, and the aluminum nitride exists in the form of fine grains. When the nitrogen pressure is greater than 1.0 MPa, the fibers are shorter, with an average length of 20-40 μm, and the fiber content is low, and the aluminum nitride mostly exists in the form of particles.

[0017] Some embodiments The effect of the aluminum powder ratio in the aluminum / aluminum nitride mixed powder on the synthesis of aluminum nitride fibers was examined. The method and steps were the same as in Example 4, with only the aluminum powder ratio being varied. The effect of the aluminum powder ratio on the synthesis of aluminum nitride fibers is shown in Table 2.

[0018] Table 2 Effect of aluminum powder proportion on the synthesis of aluminum nitride fiber Instance number Aluminum powder ratio (wt%) Is there any residual aluminum? Morphology of synthesized aluminum nitride 1 40 no fiber 2 50 no fiber 3 60 no fiber 4 70 no fiber 5 80 yes fiber Conclusion: When the aluminum powder ratio is less than 50wt%, the fibers are shorter, with an average length of 30-70μm. When the aluminum powder ratio is greater than 70%, the aluminum nitride diluent is less, which is not conducive to fiber growth, and the fibers are shorter, with an average length of 30-60μm.

[0019] Some embodiments The effect of preheating temperature on the synthesis of aluminum nitride fibers was examined. The method and steps were the same as in Example 4, with only the preheating temperature being changed. The effect of preheating temperature on the synthesis of aluminum nitride fibers is shown in Table 3 below.

[0020] Table 3 Effect of preheating temperature on the synthesis of aluminum nitride fibers Instance number Preheating temperature (℃) Is there any residual aluminum? Morphology of synthesized aluminum nitride 1 800 yes fiber 2 850 yes fiber 3 900 no fiber 4 950 no fiber 5 1000 no fiber 6 1100 no fiber 7 1150 no fiber 8 1200 no fiber 9 1250 no fiber 10 1300 no fiber 11 1350 no Fibers, particles 12 1400 no Fibers, particles Conclusion: When the preheating temperature is lower than 900℃, the aluminum powder produces insufficient gas phase, resulting in shorter fibers with an average length of 20-40μm. When the preheating temperature is higher than 1300℃, the aluminum powder melts and agglomerates, forming aluminum nitride particles, and the fiber content decreases.

[0021] Some embodiments The effect of aluminum powder particle size on the synthesis of aluminum nitride fibers was examined. The method and steps were the same as in Example 4, with only the aluminum powder particle size being varied. The effect of aluminum powder particle size on the synthesis of aluminum nitride fibers is shown in Table 4.

[0022] Table 4 Effect of aluminum powder particle size on the synthesis of aluminum nitride fibers Instance number Aluminum powder particle size (μm) Is there any residual aluminum? Morphology of synthesized aluminum nitride 1 1 yes Fibers, particles 2 5 yes fiber 3 10 no fiber 4 15 no fiber 5 20 no fiber 6 25 no fiber 7 30 no fiber 8 35 yes Fibers, particles 9 40 yes particles Conclusion: When the aluminum powder particle size is less than 5μm, the overly fine aluminum powder is prone to melt agglomeration, resulting in shorter fibers with an average length of 15-40μm and the presence of fine particles. When the aluminum powder particle size is greater than 30μm, fibers are difficult to grow and aluminum nitride particles are generated.

[0023] Some embodiments The effect of aluminum nitride powder particle size on the synthesis of aluminum nitride fibers was examined. The method and steps were the same as in Example 4, except that only the aluminum nitride powder particle size was changed. The effect of aluminum nitride powder particle size on the synthesis of aluminum nitride fibers is shown in Table 5.

[0024] Table 5 Effect of aluminum nitride powder particle size on the synthesis of aluminum nitride fibers Instance number Aluminum nitride powder particle size (μm) Is there any residual aluminum? Morphology of synthesized aluminum nitride 1 0.5 yes Fibers, particles 2 1 no fiber 3 3 no fiber 4 5 no fiber 5 7 no fiber 6 10 no fiber 7 13 yes Fibers, particles 8 15 yes Fibers, particles Conclusion: When the aluminum nitride powder particle size is less than 1μm, the aluminum nitride powder is prone to sintering at high temperatures, and the dispersion effect is weakened, resulting in aluminum melting and agglomeration. The fibers are short, with an average length of 20-40μm, and fine particles are present. When the aluminum nitride powder particle size is greater than 10μm, a large number of pores exist between the aluminum nitride powder particles, and the dispersion effect is weakened, resulting in aluminum melting and agglomeration. The average fiber length is 30-40μm, and fine particles are present.

[0025] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not limitations on the implementation methods of the present invention. For ordinary technicians in the relevant field, other different forms of changes or modifications can be made based on the above description. It is impossible to list all the implementation methods here. All obvious changes or modifications derived from the technical solution of the present invention are still within the scope of protection of the present invention.

Claims

1. A method for preheating and burning aluminum nitride fibers, characterized in that: The following steps are involved: Aluminum powder and aluminum nitride powder are mixed evenly, the raw materials are preheated in a low-pressure nitrogen environment, and then a combustion synthesis reaction is induced to prepare aluminum nitride fibers with an average diameter of 0.3-0.8μm and an average length of 400-800μm.

2. The method for synthesizing aluminum nitride fiber according to claim 1, characterized in that: The particle size of the aluminum powder raw material is in the range of 5-30 μm, and the particle size of the aluminum nitride powder is in the range of 1-10 μm.

3. The method for synthesizing aluminum nitride fiber according to claim 1, characterized in that: The temperature range of the preheated raw materials is 900-1300°C.

4. The method for synthesizing aluminum nitride fiber according to claim 1, characterized in that: The pressure range of the low-pressure nitrogen is 0.05-1.0 MPa.

5. The method for synthesizing aluminum nitride fiber according to claim 1, characterized in that: The ratio of the aluminum powder is in the range of 45-70wt%, and the sum of the ratios of the aluminum powder and the aluminum nitride powder is 100%.

Citation Information

Cited By

  • Super-long aluminum nitride fiber and self-generation combustion reactor high-flux preparation method thereof

    CN121250591A